Introducing The Characters Of Wayang Using Android Mobile Application - Arumsari, Galuh Ayu; , Prof.Dr.Budi Murtiyasa, M.Kom; , Drs.Sujalwo, M.Kom (2013)
Wayang according Indonesian Dictionary means something that played a Dalang or someone who played wayang, this thing is a carved image from animal skins which symbolizes the human nature. This research takes the issue of "How to design and build a wayang recognition applications based on Android mobile". The purpose of this research is to create an Android-based mobile application that has educational elements, easy to learned and understood by the public that can provide information about the wayang characters. Program development method using SDLC (System Development Life Cycle) is a method that describes the system development life cycle in the design and development of information systems. This build applications using Eclipse Indigo program to design, Corel Draw X5 and Adobe Photoshop7 for image editing and Audacity 1.3 Beta for audio editing. The result of the design is introducing the characters of wayang using android mobile application that have read-only characteristics and contains the notion of wayang, wayang history, understanding the Mahabharata, equipment wayang show, Wayang Mahabharata information and exercises that help the user in identifying and introducing wayang culture of Indonesia especially the wayang to the community and the world. The results of the application trial for user can be concluded that this application for the best resolution use mobile phone with size of 3.2 to 5 inches requires 28MB of memory and a minimum of Android Operating System Frozen Yogurt (Froyo) 2.2.